Decay of Solution of a Parabolic Equation in 2-space Dimensions (Journal of Partial Differential Equations, 1995)
We present a simple method for verifying the uniform L¹ bound and establish sharp rates of L² decay of the global solution to the initial value problem for a 2-dimensional parabolic equation.
Keywords: Decay estimates; 2D parabolic equation